2023
DOI: 10.1371/journal.pone.0284865
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and associated factors of HIV testing among college students in China: A systematic review and meta-analysis

Abstract: Background Although HIV testing is helpful for early detection and treatment of HIV, its utilization rate is low among college students in China. Understanding the acceptance and associated factors of HIV testing is the key to improve the detection rate. The purpose of the systematic review was to examine the acceptance and associated factors of HIV testing (including HIV self-testing and HIV counseling and testing services) among college students in China. Methods This systematic review was reported followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Nonetheless, some authors argue that there is a notable discrepancy in the use of HIV services among distinct demographics such as gender, age, socio-economic status, educational level, race, and others [26][27][28]. The current results revealed that gender, age, health department, and level of study were not associated with the utilisation of HIV VCT.…”
Section: Discussioncontrasting
confidence: 62%
“…Nonetheless, some authors argue that there is a notable discrepancy in the use of HIV services among distinct demographics such as gender, age, socio-economic status, educational level, race, and others [26][27][28]. The current results revealed that gender, age, health department, and level of study were not associated with the utilisation of HIV VCT.…”
Section: Discussioncontrasting
confidence: 62%